2022
DOI: 10.1002/ece3.9022
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of body size and habitat type in movement behavior in human‐dominated systems: A frog's eye view

Abstract: Animal movement is a key process that connects and maintains populations on the landscape, yet for most species, we do not understand how intrinsic and extrinsic factors interact to influence individual movement behavior. Land‐use/land‐cover changes highlight that connectivity among populations will depend upon an individual's ability to traverse habitats, which may vary as a result of habitat permeability, individual condition, or a combination of these factors. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 135 publications
(131 reference statements)
1
3
0
Order By: Relevance
“…Consistent with many previous studies on animal movement (e.g. Zalucki and Kitching, 1982;Kuefler and Haddad, 2006;Dumont et al, 2007;Dias et al, 2009;Avgar et al, 2013;Dodge et al, 2014;Murphy and Boone, 2022), we observed strong effects of resource availability on the path scale on butterfly diffusion rates. Here we discuss mainly silvery blue diffusion rate responses to resources, since we were unable to include the results of the ochre ringlet PLSR model due to poor model fit.…”
Section: Resource Impacts On Butterfly Movement Behaviorsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with many previous studies on animal movement (e.g. Zalucki and Kitching, 1982;Kuefler and Haddad, 2006;Dumont et al, 2007;Dias et al, 2009;Avgar et al, 2013;Dodge et al, 2014;Murphy and Boone, 2022), we observed strong effects of resource availability on the path scale on butterfly diffusion rates. Here we discuss mainly silvery blue diffusion rate responses to resources, since we were unable to include the results of the ochre ringlet PLSR model due to poor model fit.…”
Section: Resource Impacts On Butterfly Movement Behaviorsupporting
confidence: 91%
“…Animal movement behavior has been used in many contexts to evaluate aspects of habitat or habitat quality (e.g. Dumont et al, 2007;Korösi et al, 2008;Dias et al, 2009;Dodge et al, 2014;Crone et al, 2019;Murphy and Boone, 2022;Pugesek and Crone, 2022); however, studies of butterfly movement have rarely been applied to evaluate habitat under grazing management (Bussan, 2022; but see Schtickzelle et al, 2007;Ehl et al, 2019). We quantified withinhabitat diffusion rates to understand butterfly perceptions of habitat quality in conventional grazing, conservation grazing, and native upland prairie.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations